Performance of some Mangrove Species Planted under Sonneratia Apetala Buch.-Ham Plantations in the Coastal Belt of Bangladesh - Islam, Sk. Ahiul; Abdul Quddus Miah, Md.; Habib, Md. Ahsan (Indian Forester, 2015)
An underplanting trial with eleven mangrove species were conducted in Sonneratia apetala plantations at Rangabali island of Patuakhali district and Char Kukri-Mukri island of Bhola district, Bangladesh to observe the site-suitability and growth performance of the species. The data on survival, height and diameter growth were recorded from 21 years old matured experimental stands. Some mangrove species showed promising growth performance in the coastal belt. The highest survival was found in Aegiceras corniculatum followed by Phoenix paludosa, Excoecaria agallocha, Heritiera fomes and Xylocarpus mekongensis at Rangabali, and the highest survival in E. agallocha followed by P. paludosa, A. corniculatum, H. fomes and X. mekongensis at Char Kukri-Mukri. According to height and diameter growth, the most promising species were E. agallocha and then X. mekongensis, A. corniculatum, H. fomes and P. paludosa in both islands. Therefore, these mangrove species are suitable for raising second rotation forest crops inside S. apetala plantations for sustainable management of coastal forests in Bangladesh.